Ver e ouvir a surdocegueira : o emergir da comunicação - Rached, Sueli Fernandes da Silva (2011)
Bringing considerations about a rarely approach subject in Brazilian research, taking this study into prominence level, especially when it references to dictates inclusive society. The deafblindness refers to total and/or partial inability to see or hear, however, must be taken into consideration the possibility of existence of residual sight and/or hearing , that although their existence do not result in the possibility of using them in a similar way as those who do not have the indicated difficulties. Indeed it is a condition in which combines sight and hearing disorders in many levels, producing problems to their communication with society. The deafblind child has one of the less understood disabilities in general society. It is not a blind child who cannot hear, or a deaf child who cannot see. It is a child with multi-sensorial privations which will present restrictions to the use simultaneous of both distal senses, wherefore will be difficulties in expressing their thoughts and understanding other's thoughts, through the usual channels. Should be not left to consider that communication is a basic need for every human being and in the case of deafblindness takes peculiarities virtually unknown by society. Thus, deafblind children must present difficulties that, probably, will hold back their path to become active members of society. However they are capable to express themselves and also to receive messages sent to them. The objective of this study is seeing and hearing the deafblindness, it dedicated to the analysis of communication ways in deafblind children pre-linguistic. To support the study is outstanding the contributions of Vygotsky, Bruner, Tomasello, Chomsky, among others, who offered subsides to better understand the peculiarities of language acquisition in those children. Took part of the research ten deafblind pre-linguistic between three and ten years old, which belong to a unique institution from Pernambuco. The methodological procedures followed the recommendations of what a qualitative research should present. The data collection took place through three sources: parents interview, communication maps, direct observations of subjects during social interactions. The data analysis was performed individually and collectively, delimiting the profile of subjects communication ways. The final considerations reveal that the communication ways vary from person to person regardless age, however there is a set of communication ways more or less common, expressed by the group, which allowed developing a profile segment, furthering it points to the use of strategies that facilitates those acquisitions. This study hopes to contribute to renew the scenery of attention to the children that presents deafblindness, bringing concrete demonstrations of their development, pointing out the importance of social interaction for language acquisition